Premalignant cervical lesions in women under 30 years - Herrera, Gustavo (2015)
OBJECTIVE. To determine if both intraepithelial lesions and invasive cancer of the uterine cervix are appearing in younger women and if in them Papilloma virus infection (HPV) is more frequent. LUGAR: Honorio Delgado and Goyoneche Hospitals of Arequipa city; 828 patients were studied between February 1994 August 1998, using cytology and colposcopy; 179 guided were performed (21,6%). RESULTS: We found 136 (76%) of intraepithelial lesions (SIL), 26 cases (14,5%) of invasive cancer and 17 (9,5%) cases of negatives biopsies. Of all patients with intraepithelial lesions 57 (41,9%) were 30 years or less and 31 (54,4%) of them had histomorphological changes produced by HPV infection. In 36 patients (63,1%) the SIL found corresponded to high grade lesions. CONCLUSIONS: The prevalence of SIL in women of 30 years or less was 6,9%. In 54,4%, there were histomorphological changes produced by HPV infection. This group of women must call our attention.